Scaffolding in Business English Correspondence Classes at College Level - Widjojokoesoemo, Eric Sulindra (Beyond Words, 2015)
Language teaching and education have been so long influenced by developmental psychology, namely constructivism. This idea enlightens the world of language teaching. Constructivism has received both praises and critics. Communicative approach followers claim that the principles in constructivism support their thoughts while the followers of a more traditional approach, namely, Grammar Translation Method, claim that the constructivism is just another experiment in language teaching, just like other methods. This article is based on a classroom action research investigation of how scaffolding instruction, the operational ‘terms’ of constructivism, based on its ‘ZPD’ (Zone of Proximal Development), play roles in language teaching, specifically in Business English Writing. The investigation has perceived several important aspects in scaffolding instruction for teaching Business English Correspondence, such as the importance of modeling or giving examples, as well as corrective and immediate feedback, together with positive reinforcement, to improve the learners’ performance. It showed that modeling or giving examples, peer reviewing, together with immediate feedback, brought significant influence on the learners’ perspective, about their learning performance. Keywords: constructivism, Scaffolding, ZPD, Business English Writing